Factors associated with risk scores among stone mortar workers exposed to high noise levels in Lampang province, Thailand - Khunsaard, Yuwadee; Ketsakorn, Arroon (Intelektual Pustaka Media Utama, 2025)
Noise pollution is an undesirable phenomenon that affects human health and can lead to occupational hearing loss. This study was to assess associations of risk scores from exposure to noise related to their variables from noise exposure among stone mortar workers who exposed to high noise levels during their work in Lampang, Thailand. The study was conducted between August and September 2023. Data collection involved using standardized questionnaires which were developed by researchers and used scientific instruments for noise measurement. The questionnaires contained items related to population characteristics and work information, knowledge, attitude, and practice for preventing noise exposure, noise exposure measurement, and risk scores from exposure to noise. Pearson’s correlation coefficient was used to analyze data. The results showed that seven factors significantly associated with risk scores from exposure to noise while performing their work. Apparently, there were four influential variables which included height of workers, ear symptoms, working hour per day, and noise measurement as tested using multiple regression analysis. Therefore, efforts should be made to manage those variables by drafting policies and creating tools for risk prediction to control the influential variables related to risk level from exposure to noise in the working area.